Calcium Release Deficiency Syndrome (CRDS): Rethinking “Atypical” Catecholaminergic Polymorphic Ventricular Tachycardia - Alessandra P. Porretta; Etienne Pruvot; Zahurul A. Bhuiyan (Cardiogenetics)
Since the first description of catecholaminergic polymorphic ventricular tachycardia (CPVT) in the 1970s, new insights have progressively unraveled the understanding of this inherited arrhythmia syndrome. The identification of new distinct clinical entities related to RYR2, the gene encoding the cardiac ryanodine receptor, has allowed significant refinement in the diagnosis of previously labeled “atypical” CPVT cases. Among RYR2-ryanodinopathies, the characterization of calcium release deficiency syndrome (CRDS) is still in its infancy and represents a diagnostic challenge due to the need for functional studies which may confirm the loss-of-function nature of the RYR2 variant. The present review summarizes current evidence on CRDS. First, by providing an overview on RYR2 structure and function, we will elucidate the different pathophysiological underpinnings of CRDS and CPVT. Second, by retrieving in detail reported CRDS variants and their clinical phenotypes, we will provide, if any, genetic and clinical red flags that should raise suspicion for CRDS in daily clinical practice. Finally, we will discuss available therapies to provide clinicians with practical therapeutic options for CRDS management.